Representasi Makna Puisi “Anyelir” dalam Antologi “Jalang” Karya Putri Meyda : Kajian Semiotika Roland Barthes - Shalih, Moh (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study tries to represent the meaning of a poem entitled "Anyelir" in the poetry anthology entitled "Jalang" by Putri Meyda using Roland Barthes' semiotic reading code surgery theory. The type of this research is descriptive qualitative, which is one type of research that displays data in the form of descriptive phenomena without using statistics/numbers. The data collection method in this study is the content analysis/content analysis method using the reading and note-taking technique, while the data analysis method of this study is the matching method. The results of this study are that the poem entitled "Anyelir" is an expression of the feelings of the lyricist about someone's emotional experience, the poem describes inner destruction, emotional conflict, betrayal, and fatigue, and mental chaos.keyword: Anyelir, reading code, meaning